Serologic and molecular biology analysis of a rare Pk phenotype - GAO Huanhuan; ZHANG Na; GENG Wei; KONG Fansheng (Zhongguo shuxue zazhi)
[Objective] To analyze the serological characteristics and molecular biology results for a Pk phenotype. [Methods] One patient with Pk phenotype upon unexpected antibodies at Jining Blood Center in July 2022 was selected as the study subject. The blood groups and unexpected antibodies of the proband and his second son were identified using serological methods. The sequences of 3-β-N-acetylgalactosaminyltransferase gene (B3GALNT1) and the coding region of α-1,4-galactosyltransferase gene (A4GALT) were amplified and analyzed by PCR direct sequencing, and haploid sequence analysis was carried out on the variant sites of the B3GALNT1 gene. PROVEAN, SIFT, PolyPhen2 and Mutation Taster were used to analyze the effect of mutations on the protein. [Results] Serological test results suggested that the proband was a P2k type, including anti-P antibody in his serum, and his son was the P2 phenotype. Sequencing analysis revealed that the proband had a compound heterozygous variants of the B3GALNT1 in c. 239T>A (p. Leu80Gln) and c. 433C>T (p. Arg145Ter). Further haploid analysis showed that the c. 239T>A had occurred in one haploid while c. 433C>T was present in the other haploid, and his son carried a heterozygous variant of c. 433C>T (p. Arg145Ter); the proband and his son all have homozygous mutation variants of the A4GALT in c. 903C>G. Bioinformatic analysis also predicted that the mutations were harmful to the protein function. [Conclusion] The compound heterozygous variants c. 239T>A (p. Leu80Gln) and c. 433C>T (p. Arg145Ter) in the B3GALNT1 gene may contribute to the Pk phenotype, of which the c. 239T>A variant has not been reported.